Improvement of cattle productivity through rapid alleviation of African animal trypanosomiasis by integrated disease management practices in the agropastoral zone of Yale, Burkina Faso - Bauer, B.; Amsler-Delafosse, S.; Kabore, I.; Kamuanga, M. (Springer, 1999)
Investigations to identify the causes of high mortalities in cattle in the agropastoral zone (ZAP( of Yale started in March 1993. African animal trypanosomosis (AAT) was found to be the major constraint, with incidence rates exceeding 30 percent, justifying a tsetse control programme, which started in March/April 1994. The treatment of all cattle at bimonthly intervals with deltamethrin 1 percent pour on and the display of 1500 insecticide impregnated targets during the 6 months of the dry season each year helped to reduce the tsetse populations (Glossina tachinoides and G. morsitans submorsitans) by more than 90 percent. In less than 7 months, the incidence of AAt dropped below 5 percent and remained there throughout the intervention until June 1996, in spite of an increase to 3 months in the interval between the treatments. Mean PCV values increased significantly from 26.5-30.9 percent, before, to 30.7-36.3 percent during the intervention. The improvement in the overall health resulted in a resumption in fertility and milk production, allowing the sale of dairy products in Leo, thus creating a gross income of about $US3/day for the Fulani women.